HUBUNGAN PARTISIPASI REMAJA DALAM KEGIATAN PELAYANAN KESEHATAN PEDULI REMAJA (PKPR) DENGAN PENGETAHUAN DAN PERSEPSI MENGENAI KESEHATAN REPRODUKSI DI SEKOLAH MENENGAH PERTAMA WILAYAH KERJA PUSKESMAS LEBDOSARI - Nurul Desita Sari; Syamsulhuda Budi Musthofa; Bagoes Widjanarko (Jurnal Kesehatan Masyarakat (Undip), 2017)
PKPR (Teenagers Health Care Services) is the government effort to help adolescent’s problem and it is held by health center. Although PKPR implementation has been held, the coverage of PKPR service in Lebdosari Health Center is still below the target so there is increasing in adolescent reproduction health problem and health officers have difficulty taking preventive action. Adolescent perception is one of the causes of less adolescents participation in PKPR activities. The aim of this research was to analyze the correlation of adolescents participation PKPR activities with knowledge and perception about reproduction health in Junior High School at working area of Lebdosari Health Center. This was a quantitative research with cross sectional approach. Population of this research were Junior High School students in VIII grade at working area of Lebdosari Health Center with the total of 1.040 students then 91 samples were obtained using proportional random sampling method. Data was collected using interview with questionnaire. Data analysis was using univariate and bivariate with chi square at significance level of 95%. The results showed that dependent varible which correlate with adolescents participation were knowledge about PKPR (p=0,000), perceived susceptibility (p=0,000), perceived benefit (p=0,005), and perceived barrier (p=0,007). While dependent variable which not correlate with  adolescents participation were perceived severity and cues to action.  It can be concluded that there were 4 of 6 dependent variables which correlate with adolescents participation in PKPR activities and most of the respondents (61,5%) were less in adolescents participation in PKPR activities.